Correction: Factors influencing appropriate use of interventions for management of women experiencing preterm birth: A mixed-methods systematic review and narrative synthesis. - Rana Islamiah Zahroh; Alya Hazfiarini; Katherine E Eddy; Joshua P Vogel; Ӧzge Tunçalp; Nicole Minckas; Fernando Althabe; Olufemi T Oladapo; Meghan A Bohren (PLoS Medicine, 2022)
[This corrects the article DOI: 10.1371/journal.pmed.1004074.].